Analisis Mekanisme Pasar Tradisional di Tinjau dari Etika Bisnis Islam - Mariatul Fitri (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2019)
Mandau Raya Duri traditional market is very strategic because it is located in the center of the urban area. The Duri traditional market is occupied by approximately 954 traders who sell a variety of commodities including vegetables, meat, household appliances, food, clothing and others. Based on observations, traditional market traders found in the Duri traditional market are Minang, Batak, Malay and Javanese. It is this diversity that makes the Duri traditional market more attractive. There are various ethnicities in a business activity to advance the existence of the traditional market itself. Based on this it is also the cause of fraud. Frauds that violate the mechanism of the milk market with Islamic business ethics include pricing, business competition, reducing scales, and selling products that are not suitable for consumption.